2020
DOI: 10.1002/slct.202001470
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric Sensing of Hydrogen Peroxide Using Ionic‐Liquid‐Sensitized Zero‐Valent Copper Nanoparticle (nZVCu)

Abstract: In this study, a stable ionic liquid (IL) mediated zero-valent copper nanoparticle (nZVCu), namely IL-nZVCu, has been evaluated for catalytic properties towards H 2 O 2 -mediated TMB (3, 3',5,5'-tetramethylbenzidine) reaction under normal conditions of temperature and pH. The various analytical techniques like Fourier Transform Infrared Spectroscopy (FT-IR), UV-Vis diffuse reflectance spectroscopy (UV-Vis DRS), X-ray powder diffraction (XRD), scanning electron microscope (SEM), Transmission electron microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…The lower detection limit (LOD) was calculated for H 2 O 2 to be 6.36 nM using the equation LOD = 3σ/s and a limit of quantification (LQD = 10σ/s) of 21.21 nM where s represents the slope of the calibration curves in Figure c (inset), and σ is the standard deviation of 10 blank tests ( n = 10). Comparing these findings with previously developed methods (Table ), ,, the detection of H 2 O 2 using the Meso-Cu-PBMCs showed a faster response time, lower LOD, and a wider linear range, indicating a higher sensitivity for H 2 O 2 detection. Additionally, the observed multicolor variation enables easy detection of H 2 O 2 even at low concentrations, providing a simple approach.…”
Section: Resultssupporting
confidence: 69%
“…The lower detection limit (LOD) was calculated for H 2 O 2 to be 6.36 nM using the equation LOD = 3σ/s and a limit of quantification (LQD = 10σ/s) of 21.21 nM where s represents the slope of the calibration curves in Figure c (inset), and σ is the standard deviation of 10 blank tests ( n = 10). Comparing these findings with previously developed methods (Table ), ,, the detection of H 2 O 2 using the Meso-Cu-PBMCs showed a faster response time, lower LOD, and a wider linear range, indicating a higher sensitivity for H 2 O 2 detection. Additionally, the observed multicolor variation enables easy detection of H 2 O 2 even at low concentrations, providing a simple approach.…”
Section: Resultssupporting
confidence: 69%
“…An effective NP-based sensor shows a linear response to minor changes in analyte concentration Table presents a comparison of the proposed work with the previous studies reported in the literature, which gives a proof of concept that our designed sensor can work at higher as well as lower concentrations. These observations were also compared with the previous study for H 2 O 2 detection based on double molecular recognition, and the results were comparable to our proposed sensor …”
Section: Resultsmentioning
confidence: 99%
“…However, CuNPs are highly susceptible to oxidation, which causes a loss in their properties and sensing ability. 66,67 So, synthesis of stabilized CuNPs is a challenging process and some researchers have synthesized stable CuNPs and used as a probe for portable colorimetric sensing application.…”
Section: Nanomaterials Used As Colorimetric Sensing Probesmentioning
confidence: 99%